Maternal factors regulating preterm infants' responses to pain and stress while in maternal kangaroo care Los factores maternos regula la respuesta al dolor y al estrés del recién nacido en posición canguro Fatores maternos influenciam a resposta à dor e ao estresse do neonato em posição canguru - Thaíla Corrêa Castral; Fay Fathalee Warnock; Laiane Medeiros Ribeiro; Maria Gorete Lucena de Vasconcelos; Adriana Moraes Leite; Carmen Gracinda Silvan Scochi (Universidade de São Paulo, 2012)
The relationship between maternal factors and the response of preterm infants to pain and stress experienced during heel puncture while in maternal kangaroo care was investigated. This descriptive study included 42 mothers and their preterm infants cared for in a neonatal unit. Data were collected in the baseline, procedure, and recovery phases. We measured the neonates' facial actions, sleep and wake states, crying, salivary cortisol levels, and heart rate, in addition to the mothers' behavior, salivary cortisol levels, and mental condition. The influence of the maternal explanatory variables on the neonatal response variables were verified through bivariate analysis, ANOVA, and multiple regression. The mothers' behavior and depression and/or anxiety did not affect the neonates' responses to pain and stress, though the mothers' levels of salivary cortisol before the procedure explained the variance in the neonates' levels of salivary cortisol after the procedure (p=0.036). Additionally, the mothers' baseline levels of salivary cortisol along with the neonates' age explained the variance in the neonates' heart rate (p=0.001). The ability of mothers to regulate their own stress contributed to the infants' responses to pain and stress. Asociación entre los factores maternos y la respuesta de los prematuros sometidos a punción del calcáneo en posición canguro. Estudio descriptivo envolviendo 42 madres y prematuros de una unidad neonatal. La colecta se dio en el período basal, procedimiento y recuperación. Se midieron la mímica facial, sueño y vigilia, llanto, cortisol salival y frecuencia cardíaca neonatal; y el comportamiento, cortisol salival y estado mental materno. Se analizó la influencia de las variables maternas en las variables neonatales por análisis bi-variada, análisis de variancia y regresión múltiple. La depresión, ansiedad y comportamiento materno no influenciaron la respuesta del prematuro al dolor. El cortisol pre-punción materna explico la variancia del cortisol post-punción neonatal (p=0,036); el cortisol nocturno materno, juntamente con la edad post nacimiento neonatal, explicaron la variancia de la frecuencia cardíaca neonatal (p=0,001). La capacidad de las madres en regular su proprio estrés contribuyó para la respuesta del dolor del prematuro. Investigou-se associação entre fatores maternos e resposta de prematuros submetidos à punção de calcâneo em posição canguru. Trata-se de estudo descritivo envolvendo 42 mães e prematuros de uma unidade neonatal. A coleta ocorreu nos períodos basal, procedimento e recuperação. Mensuraram-se a mímica facial, sono e vigília, choro, cortisol salivar e frequência cardíaca neonatais, além de se mensurar o comportamento, cortisol salivar e estado mental maternos. Analisou-se a influência das variáveis explanatórias maternas nas variáveis de resposta neonatais por análise bivariada, análise de variância e regressão múltipla. A depressão e/ou ansiedade e comportamento materno não influenciaram a resposta do prematuro à dor e estresse. O cortisol salivar pré-punção materno explicou a variância do cortisol salivar pós-punção neonatal (p=0,036); e o cortisol salivar noturno materno, juntamente com a idade pós-natal neonatal, explicaram a variância da frequência cardíaca neonatal (p=0,001). A capacidade das mães em regular seu próprio estresse contribuiu para resposta de dor e estresse do prematuro.